Covalent Functionalization of Graphene by Nucleophilic Addition Reaction: Synthesis and Optical‐Limiting Properties. Issue 19 (8th September 2017) - Xu, Xiujuan; Li, Peiying; Zhang, Lei; Liu, Xuejian; Zhang, Hao‐Li; Shi, Qingzhao; He, Baojiang; Zhang, Wenjuan; Qu, Zhan; Liu, Pu
Abstract: Covalent functionalization of reduced graphene oxide (rGO) was performed by using conjugated polymers with different monomers through nucleophilic addition of nitrogen anions to rGO. Three conjugated polymers containing tetraphenylethylene, carbazole, and phenyl groups were used, and as a result of π–π interactions and the "polymer‐wrapping" effect, the dispersion stability of rGO was improved. Even if the reaction site in the polymers was the same, there were great differences in the reactivities of the polymers, the dispersion stabilities of the resultant composites, and also the optical limiting (OL) performances of the resultant composites. The differences may be attributed to the π‐conjugated structure and steric hindrance of the moiety in the polymer skeleton, which has scarcely been reported. Besides, the resultant rGO‐P1 and rGO‐P3 materials both showed excellent OL responses, even at 4 μJ. This behavior should enable their potential application in photonic and optoelectronic devices to protect human eyes or optical sensors from damage by intense laser irradiation. Abstract : The same but different : Reduced graphene oxide (rGO) is covalently functionalized through nucleophilic addition of different conjugated polymers having the same reacting site but different monomers. Great differences are found in the reactivities of the polymers, the dispersion stabilities of the resultant composites, and the optical‐limiting performances of the resultant composites.